2015
DOI: 10.3892/mco.2015.657
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the long non-coding RNA metastasis-associated lung adenocarcinoma transcript 1 in various cancers: A meta-analysis

Abstract: Several studies have investigated the correlation between the expression of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) and cancer prognosis, with inconsistent results. Therefore, a meta-analysis was conducted to identify the potential correlation after pooling data from eligible studies. PubMed/Medline, Web of Science and The Cochrane Library electronic databases were searched for eligible studies on the prognostic role of MALAT1 in cancer, from inception to January, 2015. Pooled hazard ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…MALAT1 is involved with the survival of various tumor types and may act as a valid prognostic biomarker for cancer ( 34 ). A previous study revealed its role in extensive biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…MALAT1 is involved with the survival of various tumor types and may act as a valid prognostic biomarker for cancer ( 34 ). A previous study revealed its role in extensive biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Additional published studies on MALAT1 in UC are difficult to compare as only small sample numbers were investigated and information on histopathological characteristics is not comprehensive [ 26 ]. Two meta-analyses of 10 studies on MALAT1 in various cancer types indicated a relatively consistent association of increased MALAT1 expression with survival in various types of cancer, but some studies analysed only few cases [ 36 , 37 ]. Clearly, further studies on MALAT1 should be conducted to ascertain the association of its expression with tumour subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…[46] Moreover, aberrant lncRNA expression was found to lead to metastasis and cancer progression. [79] The lncRNAs such as urothelial cancer associated 1 (UCA1), [10] metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), [11] H19, [12] and PVT1 [13] were found to predict lymph node metastasis (LNM) and a poor prognosis in human cancers. Recently, the lncRNA small nucleolar RNA host gene 1 (SNHG1) was found to be high-expressed and functioned as an oncogene in various cancers, such as nonsmall-cell lung cancer, [14] gastric cancer, [15] and colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%